Find expert answers and community-driven knowledge on IDNLearn.com. Get comprehensive answers to all your questions from our network of experienced experts.
Sagot :
Sure, let's solve these equations step-by-step using the Monge method.
### Given Equations:
1. [tex]\( 3s + (rt - s^2) = 2 \)[/tex]
2. [tex]\( 3s - 2(rt - s^2) = 2 \)[/tex]
### Equation (i): [tex]\( 3s + (rt - s^2) = 2 \)[/tex]
Let's start by solving for [tex]\( s \)[/tex] in the first equation:
[tex]\[ 3s + rt - s^2 = 2 \][/tex]
Rearrange the terms to form a quadratic equation:
[tex]\[ s^2 - 3s + 2 - rt = 0 \][/tex]
Now, this is a standard quadratic equation in [tex]\( s \)[/tex] of the form [tex]\( As^2 + Bs + C = 0 \)[/tex], where:
[tex]\[ A = 1 \][/tex]
[tex]\[ B = -3 \][/tex]
[tex]\[ C = 2 - rt \][/tex]
The solutions to the quadratic equation [tex]\( As^2 + Bs + C = 0 \)[/tex] are given by the quadratic formula:
[tex]\[ s = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \][/tex]
Substitute the values of [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex]:
[tex]\[ s = \frac{-(-3) \pm \sqrt{(-3)^2 - 4 \cdot 1 \cdot (2 - rt)}}{2 \cdot 1} \][/tex]
[tex]\[ s = \frac{3 \pm \sqrt{9 - 8 + 4rt}}{2} \][/tex]
[tex]\[ s = \frac{3 \pm \sqrt{1 + 4rt}}{2} \][/tex]
Therefore, the solutions for [tex]\( s \)[/tex] in the first equation are:
[tex]\[ s_1 = \frac{3 + \sqrt{1 + 4rt}}{2} \][/tex]
[tex]\[ s_2 = \frac{3 - \sqrt{1 + 4rt}}{2} \][/tex]
Given specific values [tex]\( r = 1 \)[/tex] and [tex]\( t = 1 \)[/tex]:
[tex]\[ s_1 = \frac{3 + \sqrt{1 + 4 \cdot 1 \cdot 1}}{2} = \frac{3 + \sqrt{5}}{2} \approx 2.618 \][/tex]
[tex]\[ s_2 = \frac{3 - \sqrt{1 + 4 \cdot 1 \cdot 1}}{2} = \frac{3 - \sqrt{5}}{2} \approx 0.382 \][/tex]
### Equation (ii): [tex]\( 3s - 2(rt - s^2) = 2 \)[/tex]
Next, let's solve for [tex]\( s \)[/tex] in the second equation:
[tex]\[ 3s - 2(rt - s^2) = 2 \][/tex]
Rearrange the terms to form a quadratic equation:
[tex]\[ 3s - 2rt + 2s^2 = 2 \][/tex]
[tex]\[ 2s^2 + 3s - 2rt = 2 \][/tex]
[tex]\[ 2s^2 + 3s - 2(rt + 1) = 0 \][/tex]
This is a quadratic equation in [tex]\( s \)[/tex] of the form [tex]\( As^2 + Bs + C = 0 \)[/tex], where:
[tex]\[ A = 2 \][/tex]
[tex]\[ B = 3 \][/tex]
[tex]\[ C = -2(rt + 1) \][/tex]
The solutions to the quadratic equation [tex]\( As^2 + Bs + C = 0 \)[/tex] are given by:
[tex]\[ s = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \][/tex]
Substitute the values of [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex]:
[tex]\[ s = \frac{-3 \pm \sqrt{3^2 - 4 \cdot 2 \cdot (-2(rt + 1))}}{2 \cdot 2} \][/tex]
[tex]\[ s = \frac{-3 \pm \sqrt{9 + 16(rt + 1)}}{4} \][/tex]
[tex]\[ s = \frac{-3 \pm \sqrt{9 + 16rt + 16}}{4} \][/tex]
[tex]\[ s = \frac{-3 \pm \sqrt{25 + 16rt}}{4} \][/tex]
Therefore, the solutions for [tex]\( s \)[/tex] in the second equation are:
[tex]\[ s_1 = \frac{-3 + \sqrt{25 + 16rt}}{4} \][/tex]
[tex]\[ s_2 = \frac{-3 - \sqrt{25 + 16rt}}{4} \][/tex]
Given the specific values [tex]\( r = 1 \)[/tex] and [tex]\( t = 1 \)[/tex]:
[tex]\[ s_1 = \frac{-3 + \sqrt{25 + 16 \cdot 1 \cdot 1}}{4} = \frac{-3 + \sqrt{41}}{4} \approx 0.851 \][/tex]
[tex]\[ s_2 = \frac{-3 - \sqrt{25 + 16 \cdot 1 \cdot 1}}{4} = \frac{-3 - \sqrt{41}}{4} \approx -2.351 \][/tex]
### Summary of Solutions
For the given equations, the solutions for [tex]\( s \)[/tex] are:
1. [tex]\( 3s + (rt - s^2) = 2 \)[/tex]:
[tex]\( s_1 \approx 2.618 \)[/tex]
[tex]\( s_2 \approx 0.382 \)[/tex]
2. [tex]\( 3s - 2(rt - s^2) = 2 \)[/tex]:
[tex]\( s_1 \approx 0.851 \)[/tex]
[tex]\( s_2 \approx -2.351 \)[/tex]
### Given Equations:
1. [tex]\( 3s + (rt - s^2) = 2 \)[/tex]
2. [tex]\( 3s - 2(rt - s^2) = 2 \)[/tex]
### Equation (i): [tex]\( 3s + (rt - s^2) = 2 \)[/tex]
Let's start by solving for [tex]\( s \)[/tex] in the first equation:
[tex]\[ 3s + rt - s^2 = 2 \][/tex]
Rearrange the terms to form a quadratic equation:
[tex]\[ s^2 - 3s + 2 - rt = 0 \][/tex]
Now, this is a standard quadratic equation in [tex]\( s \)[/tex] of the form [tex]\( As^2 + Bs + C = 0 \)[/tex], where:
[tex]\[ A = 1 \][/tex]
[tex]\[ B = -3 \][/tex]
[tex]\[ C = 2 - rt \][/tex]
The solutions to the quadratic equation [tex]\( As^2 + Bs + C = 0 \)[/tex] are given by the quadratic formula:
[tex]\[ s = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \][/tex]
Substitute the values of [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex]:
[tex]\[ s = \frac{-(-3) \pm \sqrt{(-3)^2 - 4 \cdot 1 \cdot (2 - rt)}}{2 \cdot 1} \][/tex]
[tex]\[ s = \frac{3 \pm \sqrt{9 - 8 + 4rt}}{2} \][/tex]
[tex]\[ s = \frac{3 \pm \sqrt{1 + 4rt}}{2} \][/tex]
Therefore, the solutions for [tex]\( s \)[/tex] in the first equation are:
[tex]\[ s_1 = \frac{3 + \sqrt{1 + 4rt}}{2} \][/tex]
[tex]\[ s_2 = \frac{3 - \sqrt{1 + 4rt}}{2} \][/tex]
Given specific values [tex]\( r = 1 \)[/tex] and [tex]\( t = 1 \)[/tex]:
[tex]\[ s_1 = \frac{3 + \sqrt{1 + 4 \cdot 1 \cdot 1}}{2} = \frac{3 + \sqrt{5}}{2} \approx 2.618 \][/tex]
[tex]\[ s_2 = \frac{3 - \sqrt{1 + 4 \cdot 1 \cdot 1}}{2} = \frac{3 - \sqrt{5}}{2} \approx 0.382 \][/tex]
### Equation (ii): [tex]\( 3s - 2(rt - s^2) = 2 \)[/tex]
Next, let's solve for [tex]\( s \)[/tex] in the second equation:
[tex]\[ 3s - 2(rt - s^2) = 2 \][/tex]
Rearrange the terms to form a quadratic equation:
[tex]\[ 3s - 2rt + 2s^2 = 2 \][/tex]
[tex]\[ 2s^2 + 3s - 2rt = 2 \][/tex]
[tex]\[ 2s^2 + 3s - 2(rt + 1) = 0 \][/tex]
This is a quadratic equation in [tex]\( s \)[/tex] of the form [tex]\( As^2 + Bs + C = 0 \)[/tex], where:
[tex]\[ A = 2 \][/tex]
[tex]\[ B = 3 \][/tex]
[tex]\[ C = -2(rt + 1) \][/tex]
The solutions to the quadratic equation [tex]\( As^2 + Bs + C = 0 \)[/tex] are given by:
[tex]\[ s = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \][/tex]
Substitute the values of [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex]:
[tex]\[ s = \frac{-3 \pm \sqrt{3^2 - 4 \cdot 2 \cdot (-2(rt + 1))}}{2 \cdot 2} \][/tex]
[tex]\[ s = \frac{-3 \pm \sqrt{9 + 16(rt + 1)}}{4} \][/tex]
[tex]\[ s = \frac{-3 \pm \sqrt{9 + 16rt + 16}}{4} \][/tex]
[tex]\[ s = \frac{-3 \pm \sqrt{25 + 16rt}}{4} \][/tex]
Therefore, the solutions for [tex]\( s \)[/tex] in the second equation are:
[tex]\[ s_1 = \frac{-3 + \sqrt{25 + 16rt}}{4} \][/tex]
[tex]\[ s_2 = \frac{-3 - \sqrt{25 + 16rt}}{4} \][/tex]
Given the specific values [tex]\( r = 1 \)[/tex] and [tex]\( t = 1 \)[/tex]:
[tex]\[ s_1 = \frac{-3 + \sqrt{25 + 16 \cdot 1 \cdot 1}}{4} = \frac{-3 + \sqrt{41}}{4} \approx 0.851 \][/tex]
[tex]\[ s_2 = \frac{-3 - \sqrt{25 + 16 \cdot 1 \cdot 1}}{4} = \frac{-3 - \sqrt{41}}{4} \approx -2.351 \][/tex]
### Summary of Solutions
For the given equations, the solutions for [tex]\( s \)[/tex] are:
1. [tex]\( 3s + (rt - s^2) = 2 \)[/tex]:
[tex]\( s_1 \approx 2.618 \)[/tex]
[tex]\( s_2 \approx 0.382 \)[/tex]
2. [tex]\( 3s - 2(rt - s^2) = 2 \)[/tex]:
[tex]\( s_1 \approx 0.851 \)[/tex]
[tex]\( s_2 \approx -2.351 \)[/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Your questions find clarity at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.